Panel Modelling to Analyze Financial Performance On Islamic Commercial Banks - Fuad Hasyim; Ningrum, Andini Dwi Kusuma; Robbani, Jundi Fikri (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research was conducted to determine the influence of CAR, NOM, OCR, FDR on Islamic Commercial Banks for the 2016-2020 period. The population of this study was all Sharia Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) in 2016-2020 and obtained 12 samples that met the criteria using purposive sampling techniques. The data analysis technique uses multiple linear regression techniques of panel data with the selection of a Fixed Effect Model (FEM). The results showed that: (1) CAR has a positive effect on ROA in Islamic Commercial Banks. (2) NOM has a positive effect on ROA in Islamic Commercial Banks. (3) OCR has a positive effect on ROA. (4) FDR has a positive effect on the ROA of Islamic Commercial Banks.